2002
DOI: 10.1007/bf02704595
|View full text |Cite
|
Sign up to set email alerts
|

Cast iron deterioration with time in various aqueous salt solutions

Abstract: The changes with time in the corrosion rate and corrosion current density on a cast iron electrode in various aqueous salt solutions have been carried out using total immersion test and potentiostatic polarization curves. The concentration of salts taken is expected to be present in potable water. The relative behaviour of these salts towards corrosion has also been studied, which is found to be different from previous studies. The total immersion test parameters viz. weight loss, corrosion rate as well as pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
2
21
1
Order By: Relevance
“…E-mail: kassiazzoug@gmail.com Overseas Foundry are in relation to the nucleation process and morphological transformations of graphite. The latter is dependent on the tensile strength of the cast iron (cracking sites) and the corrosion behavior in some corrosive environments [7,10,[19][20][21][22] .…”
Section: *M O Azzougmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: kassiazzoug@gmail.com Overseas Foundry are in relation to the nucleation process and morphological transformations of graphite. The latter is dependent on the tensile strength of the cast iron (cracking sites) and the corrosion behavior in some corrosive environments [7,10,[19][20][21][22] .…”
Section: *M O Azzougmentioning
confidence: 99%
“…Mohebbi et al [25] found that localized corrosion (pitting) is the main form of corrosion in cast iron water pipes. Mehra et al [19] investigated the variation in corrosion rate and corrosion current density of gray cast iron as a function of immersion time in various salt solutions. These authors found that the NaCl solution is the most corrosive to cast iron.…”
Section: *M O Azzougmentioning
confidence: 99%
“…A lot of experimental studies of cast iron for practical use were conducted. [2][3][4][5][6][7][8][9] However, few reports on the basic corrosion mechanism of cast iron have been published. To elucidate mechanisms of corrosion of cast iron, intensive studies on each process are important.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of experimental studies of cast iron for practical use were conducted [1][2][3][4][5][6][7][8]. A form of corrosion unique to cast irons is a selective leaching attack commonly referred to as graphitic corrosion [9, page 89].…”
Section: Introductionmentioning
confidence: 99%